Annual Tribal Sub-Plan 1985-86 Government of Tamil Nadu - Planning Commission (Planning Commission, 1985)
The Late Prime Minister of India Smt. Indira Gandhi emphasized on the need to pay special attention to the development of the weaker sections of the population, among them the Scheduled Tribes. She has stressed that the tribal communities, living, as many of them do, in remote and inaccessible areas and in primitive conditions call for our special attention. Point No.7 of the late Prime Minister’s New 20 Point Economic Programme also lays emphasis on the acceleration of the development of Scheduled Tribes enabling targeted number of families to cross the poverty line through a package of programmes.
Government of Tamil Nadu
Government of Tamil Nadu